Shared knowledge centre (research and education centre) of the Peoples’ Friendship University of Russia as a modern experimental basis for the development of drug standards - R. A. Abramovich; O. G. Potanina; V. V. Chistyakov; S. V. Goryainov; A. N. Vorobiev; A. V. Nikulin (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Shared Knowledge Centre (Research and Education Centre) of the Peoples’ Friendship University of Russia (SKC (REC) PFUR) was established in 2009. It is equipped with modern advanced measuring and testing equipment. On the basis of SKC (REC) various scientific and research projects are conducted, such as the development and formulation of medicines; quality control and standardization of medicines and substances, etc. The research results became a basis for a number of general monographs and monographs to be included in the Russian State Pharmacopoeia XIII edition, in particular, «Mass Spectrometry», «Fatty oils» etc. At the moment the employees of SKC (REC) are developing technologies and methods of standardization for dosage forms such as transdermal patch, buccal films, floating tablet and other innovative dosage forms, which will be used for further development of the general monographs and monographs for the future Russian State Pharmacopoeia editions.